2007
DOI: 10.4028/www.scientific.net/msf.550.429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initial Austenite Microstructure on the Softening – Precipitation Interaction in a Low Nb Microalloyed Steel

Abstract: The influence of initial grain size on the softening-precipitation interaction in a low niobium microalloyed steel has been investigated. The study has revealed that for the largest initial grain size (1000 μm), the recrystallised fraction remains lower than the softening fraction until relatively long times are reached. In contrast, for the smallest initial grain size (166 μm) both magnitudes are similar. As a result, precipitation interacts with recrystallisation in the case of the finest austenite grain siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In some cases precipitates are detected on replicas before the onset of precipitation is defined by the "plateau" in the softening curve. 41,42) On the other hand, difficulties arise in separating the hardness increment owing to the precipitates from other mechanisms, such as grain size strengthening, solid solution strengthening and dislocation strengthening. 30) It has been found that microhardness measurements lead to longer periods than in chemical analysis for strain-induced precipitation measurements.…”
Section: Precipitation Constantsmentioning
confidence: 99%
“…In some cases precipitates are detected on replicas before the onset of precipitation is defined by the "plateau" in the softening curve. 41,42) On the other hand, difficulties arise in separating the hardness increment owing to the precipitates from other mechanisms, such as grain size strengthening, solid solution strengthening and dislocation strengthening. 30) It has been found that microhardness measurements lead to longer periods than in chemical analysis for strain-induced precipitation measurements.…”
Section: Precipitation Constantsmentioning
confidence: 99%
“…Initial austenite grain size has a great effect on the softening and precipitation interaction in micro-alloyed steels. 3…”
Section: Introductionmentioning
confidence: 99%
“…Initial austenite grain size has a great effect on the softening and precipitation interaction in micro-alloyed steels. 3 Prediction of material mechanical properties based on thermo-mechanical process parameters will provide the steel industry with a very useful tool. Investigations have proved that the yield and tensile strengths are affected by percentages of micro-alloying elements added to the steels and the final ferrite grain sizes.…”
Section: Introductionmentioning
confidence: 99%